Holocue: A Wearable Holographic Cueing Application for Alleviating Freezing of Gait in Parkinson's Disease - Geerse, Daphne J.; Coolen, Bert; van Hilten, Jacobus J.; Roerdink, Melvyn (Frontiers in Neurology, 2022)
External visual cueing is a well-known means to target freezing of gait (FOG) in Parkinson’s disease patients. Holocue is a wearable visual cueing application that allows the HoloLens 1 mixed-reality headset to present on-demand patient-tailored action-relevant 2D and 3D holographic visual cues in free-living environments. The aim of this study involving 24 Parkinson’s disease patients with dopaminergic ‘ON state’ FOG was twofold. First, to explore unfamiliarity and habituation effects associated with wearing the HoloLens on FOG. Second, to evaluate the potential immediate effect of Holocue on alleviating FOG in the home environment. Three sessions were conducted to examine 1) the effect of wearing the unfamiliar HoloLens on FOG by comparing walking with and without the HoloLens, 2) habituation effects to wearing the HoloLens by comparing FOG while walking with HoloLens over sessions and 3) the potential immediate effect of Holocue on FOG by comparing walking with HoloLens with and without Holocue. Wearing the HoloLens (without Holocue) did significantly increase the number and duration of FOG episodes, but this unfamiliarity effect disappeared with habituation over sessions. This not only emphasizes the need for sufficient habituation to unfamiliar devices, but also testifies to the need for research designs with appropriate control conditions when examining effects of unfamiliar wearable cueing devices. Holocue had overall no immediate effect on FOG, although objective and subjective benefits were observed for some individuals, most notably those with long and/or many FOG episodes. Our participants raised valuable opportunities to improve Holocue and confirmed our assumptions about current and anticipated future design choices, which supports ongoing Holocue development for and with end users.